A 0.8V, 16mW, 170.5dB FOM Integrated 20-GHz VCO and Frequency Tripler for 60-GHz Short-Range Radio Transmitters in 22-nm FDSOI - Gupta, Aditya; Tas, Deniz; Dietz, Marco; Hagelauer, Amelie (Asia-Pacific Microwave Conference Proceedings, APMC, 2024)
This paper presents a 60-GHz frequency generator comprising a 20-GHz LC-based VCO cascaded with class-C frequency tripler for low-power millimeter-wave transmitters. Implemented in 22-nm FDSOI CMOS, the VCO employs an NMOS cross-coupled topology cascaded with an inverter buffer chain to extract the 3rd harmonic (3fo) tone. The frequency tripler selectively amplifies the 3fo tone while attenuating the fundamental (fo) and second harmonic (2fo) tones. The measured phase noise of the 3fo tone is -87 dBc/Hz at 1 MHz carrier offset frequency. The design achieves 170.5 dB FOM and frequency tuning range of 59.2-61.2 GHz with a total DC power consumption of 16 mW at 0.8 V supply. The chip occupies 0.5 mm2area.
Created from Fastlane, Scopus look-up
Keywords: CMOS process; FDSOI; frequency multiplier; localization; millimeter wave integrated circuits; voltage-controlled oscillator